Thermohydraulic performance investigation of a heat exchanger with combined effect of ribbed insert and Therminol55/MXene+Al2O3 nanofluid : A numerical two-phase approach - Das, Likhan; Aslfattahi, Navid; Khairul, Habib; Saidur, R.; Das, Anupom; Kadirgama, Kumaran (Elsevier Ltd, 2023)
MXene-based nanofluids are novel trends with improved dispersion stability and thermophysical characteristics over previously established nanofluids. In the present work, the thermohydraulic characteristics of a double pipe heat exchanger (DPHEX) with a Therminol55(TH55)/MXene + Al2O3 nanofluid and various geometrically shaped (triangular, rectangular) ribbed twisted tape (TT) inserts are numerically investigated using the ANSYS Fluent interface. A counter flow arrangement with three different types of inserts (RRTT, TRTT, TT) and TH55/MXene + Al2O3 nanofluid at 0.20 wt% are studied inside the heat exchanger. Adding ribbed inserts to the conventional TT insert enhances the turbulence intensity by creating extra vortices. The thermal boundary layer grows thinner due to increased axial and radial velocity. Due to the substantial flow obstruction, adding ribs increases the overall pressure drop between the inlet and outlet. The maximum increase in Nu is 11.04 % using nanofluid instead of water, whereas the combination of insert and nanofluid exhibited up to 105 % enhancement for rectangular-ribbed TT compared to the plain tube. Nevertheless, the pressure decrease is found to be maximum in rectangular-ribbed TT because of significant flow disruption. This was likewise true with triangular-ribbed TT and TT insert. According to the PEC assessment, the RRTT insert had a maximum PEC value of 1.67 greater than TRTT and traditional TT for both TH55 and nanofluid flowing inside the tube. To summarize, the combination of TH55/MXene + Al2O3 RRTT insert may be a promising choice for improving heat exchanger performance in a new generation efficient thermal system.